Assessment of readiness of dental faculty and students in Kuwait to implement a smoking cessation counseling curriculum - Khalaf, Mai E. (J Int Soc Prev Community Dent, 2016)
AIMS AND OBJECTIVES: The goal of this study was to assess the readiness of both dental faculty and dental students in Kuwait to implement a smoking cessation counseling curriculum. MATERIALS AND METHODS: The study population included all faculty and students in their clinical training years at the Faculty of Dentistry, Kuwait University. The survey instrument was a 42-item questionnaire. Data analysis involved employing various methods of descriptive statistics. RESULTS: Students and faculty reported that their general knowledge of what to include in a cessation message was excellent. Students reported and anticipated more clinical barriers than did the faculty. Both students and faculty agreed strongly that they were willing to refer patients for cessation in their clinical practice, faculty were much less willing to prescribe medications for cessation as compared to students. The majority of students and faculty disagreed with the statement that performing cessation was easy. Responses showed that the use of the 5 A's has not penetrated well into clinical practice for either the students or the faculty. CONCLUSIONS: Clinical students and faculty members believe smoking cessation counseling to be effective; however, their activity was mostly limited to asking patients if they smoked and both reported their knowledge of cessation counseling to be only fair.